Optimal internal balancing adjustment of double-arm electric installations - Tereshkevych, L. B.; Sahaidak, T. Z.; Zakharov, V. V. (Visnyk of Vinnytsia Politechnical Institute, 2010)
Mathematical model of the internal balancing for double-arm units which have technological requirements for connecting them to the network is suggested in the paper. The computational method of their optimal phasing calculation is developed.